Effect of titanium binder addition on the interface structure and three-body abrasive wear behavior of ZTA ceramic particles-reinforced high chromium cast iron. Issue 9 (15th June 2020) - Zheng, Baochao; Li, Wei; Tu, Xiaohui; Xu, Fangwei; Liu, Kan; Song, Suocheng
Abstract: The effects of Ti alloy binder addition on the wettability, interface microstructure, and three-body wear behaviors of ZTA ceramic particle-reinforced composites were investigated systematically. With binder addition from 5% to 15%, molten Cr26 can wet the ZTA ceramic surface, with a wetting angle of only 17.7°. Oxygen and iron atoms diffused into the transition layer to form a metallurgical bonding interface, which enhanced the interface bonding strength and brittleness. A combined supporting effect of the Cr26 matrix on the ZTA ceramic particles and protecting effect of the ZTA ceramic particles on the matrix during wear resulted in an improvement in wear resistance. The brittleness interface harmed the wear resistance at a higher load (2 kg and 3 kg). This indicates the ZTA ceramic particles has positive influence on the wear resistance of composites.